Design and Implementation of Communication Scheme between Ethernet and Multi-Serial Port - He Xin; Wu Jia’nan; Deng Hongde; Zhen Zean; Liu Chenyang (MATEC Web of Conferences, 2018)
With the development of aerospace technology, the flight control system is getting more and more important for a UAV (Unmanned Aerial Vehicle) flying safely and efficiently. For collecting the experimental data without delay, this paper briefly reviews the design of the communication scheme, and provides the implemented results. Through using the controller LPC1768 to expand the serial port, and the Ethernet controller DP83848 to complete the communication by UDP protocol, it turns out that this method is able to reach the real-time requirements of the UAV semi-physical simulation.